Sustainability reporting to integrated reporting: the relationship between Integrated Reporting Disclosure Quality (IRDQ) and firm performance / Mira Susanti Amirrudin, Mazni Abdullah and Zakiah Saleh - Amirrudin, Mira Susanti; Abdullah, Mazni; Saleh, Zakiah (Faculty of Accountancy, 2019)
The International Integrated Reporting Council (IIRC) has developed an Integrated Reporting (IR) Framework in 2013 for better integration of financial and non-financial information and to improve corporate reporting. IR comprises financial and non-financial information and is more than the publication of one report. IIRC calls companies to prepare their annual report by IR Framework. Given the new development of IR, research should examine the actual contents of IR and the effect of this reporting strategy on performance or value. It is essential to highlight that an IR is not merely combining two reports as one. It is a holistic view of the organisation by putting its performance and prospects, strategy and governance into its external environment. Using the data of 360 firm year observations of IR companies, this study examines the quality of IR by developing an index which measures the quality of IR report and identifies if there is any relationship between IR and firm performance. The finding provides evidence that the quality of IR prepared following the IR Framework 2013 is improved from the year 2014 to 2016. There is no difference in the quality of IR between compulsory (African region) and voluntary region (other region). There is significant positive evidence in the relationship between IRDQ and firm performance. This study contributes to providing empirical evidence on the benefits of adopting the IR Framework. The IR disclosure score from this study will be significant to the preparers of IR, policy maker and standard setters to assist in assessing IR’s potential as a vehicle to improve corporate reporting after the issuance of Framework in 2013.